The morphometric acclimation to depth explains the long-term resilience of the seagrass Cymodocea nodosa in a shallow tidal lagoon. (1st December 2021) - Peralta, G.; Godoy, O.; Egea, L.G.; de los Santos, C.B.; Jiménez-Ramos, R.; Lara, M.; Brun, F.G.; Hernández, I.; Olivé, I.; Vergara, J.J.; González-Ortiz, V.; Moreno-Marín, F.; et al.
Abstract: Cadiz Bay is a shallow mesotidal lagoon with extensive populations of the seagrass Cymodocea nodosa at intertidal and shallow subtidal elevations. This work aims to understand the mechanisms behind the resilience of this species to gradual sea level rise by studying its acclimation capacity to depth along the shallow littoral, and therefore, to gradual variations in the light environment. To address this objective, these populations have been monitored seasonally over a 10 year period, representing the longest seasonal database available in the literature for this species. The monitoring included populations at 0.4, −0.08 and −0.5 m LAT. The results show that C. nodosa has a strong seasonality for demographic and shoot dynamic properties – with longer shoots and larger growth in summer (high temperature) than in winter (low temperature), but also some losses. Moreover, shoots have different leaf morphometry depending on depth, with small and dense shoots in the intertidal areas (0.4 m) and sparse large shoots in the subtidal ones (−0.08 and 0.5 m). These differences in morphometry and shoot dynamic properties, combined with the differences in shoot density, explain the lack of differences in meadow production balance (i.e. meadow growth – meadow losses) between the intertidal (0.4 m) and the deepest population (−0.5 m), supporting the long term resilience of Cymodocea nodosa in Cadiz Bay. This study contributes to the understanding of the mechanisms behind seagrass stability and resilience, which is particularly important towards predicting the effects of climate change on these key coastal ecosystems, and also highlights the value of continuous long-term monitoring efforts to evaluate seagrass trajectories. Highlights: This work presents the longest seasonal database available in literature for Cymodocea nodosa. C. nodosa acclimates to differences in light availability through morphometric changes. C. nodosa morphotypes have different growth rate and shoot density. Morphometric acclimation supports the long-term resilience of C. nodosa meadows in shallow environments. Water quality and accommodation space are going to be crucial for the adaptation of this species to Sea Level Rise.